2014
DOI: 10.1002/dmrr.2521
|View full text |Cite
|
Sign up to set email alerts
|

Short and long‐term repercussions of the experimental diabetes in embryofetal development

Abstract: Our results show that during diabetic pregnancy, preimplantation embryos present decreased cell number due to higher apoptosis rates, which are dependent of the hyperglycemic intensity. Moreover, fetal viability was also decreased suggesting that the quality of these embryos at long-term may be questioned.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 42 publications
0
3
0
2
Order By: Relevance
“…In our laboratory, to induce mild diabetes, which is characterized by low glycemic intensity, the rats received a STZ injection (dose of 100 mg/kg body weight) subcutaneously at birth. Approximately three days after STZ administration, these animals developed hyperglycemia (>300 mg/dL) and presented low blood glucose levels (120–200 mg/dL) at adulthood [ 83 , 85 93 ]. This fact might be explained by the high regenerative capacity of β -cell during the neonatal period [ 94 , 95 ].…”
Section: Diabetes and Pregnancy: Experimental Modelsmentioning
confidence: 99%
“…In our laboratory, to induce mild diabetes, which is characterized by low glycemic intensity, the rats received a STZ injection (dose of 100 mg/kg body weight) subcutaneously at birth. Approximately three days after STZ administration, these animals developed hyperglycemia (>300 mg/dL) and presented low blood glucose levels (120–200 mg/dL) at adulthood [ 83 , 85 93 ]. This fact might be explained by the high regenerative capacity of β -cell during the neonatal period [ 94 , 95 ].…”
Section: Diabetes and Pregnancy: Experimental Modelsmentioning
confidence: 99%
“…They adapt by altering insulin resistance and secretion, which impairs glucose tolerance in adult life and increases the risk of developing type 2 DM [6]. In addition, animal models have shown that diabetes can be transmitted to the fetus by intrauterine exposure to maternal hyperglycemia, which may contribute to a worldwide epidemic of diabetes, further emphasizing the need for adequate glycemic control during pregnancy [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, OD/HFD rats showed a decrease in the number of implantations and live fetuses and higher rates of embryonic losses before implantation. Studies with early embryos (from two cells to blastocyst) in culture with high mean glucose concentration ( Fraser et al, 2007 ) or in vivo study using hyperglycemic mother rats to evaluate their pre-embryos ( Bueno et al, 2014 ) showed damages caused by hyperglycemic exposure during early embryonic development. This led to reduced cell numbers and increased apoptosis rates, which caused developmental delay and affected the success of embryonic implantation.…”
Section: Discussionmentioning
confidence: 99%